Electromechanical Analysis of the Medium Voltage Earthing Switch due to Short-Time and Peak Withstand Current Test - Maja Krčum; Marko Zubčić; Tatijana Dlabač (Energies, 2019)
The chosen electrical equipment, i.e., the earthing switch has its application in marine switchgear. In this paper, the reduction of dimensions is considered with the purpose of making it more energy efficient in terms of onboard application. This test validates that the earthing switch as an electromechanical device is capable of withstanding electrodynamic forces. Two approaches are applied and compared. Both approaches are based on a simplified three-dimensional (3D) model of the earthing switch. The first approach is analytical: the electrodynamic forces are calculated with the assumption that currents flow in concentrated lines. Maximum static stress is compared to the yield point of the earthing knife material. The second approach applies the finite element method in the time domain. The results show that the rectangular cross-section can withstand the electrodynamic forces produced by the given currents. Simple cost analysis shows how much material is saved by changing the design from standard earthing knifes with C channel profile to the rectangular profile. Material savings make this study interesting for marine switchgear application. The paper shows qualitative influence of the obtained results on the Energy Efficiency Design Index of the ships.